Analisis Momentum Hari Raya Idul Fitri pada Emiten Sektor Food and Beverage di Pasar Modal Indonesia - Devid Saputra (Institut Agama Islam Agus Salim Metro Lampung, 2020)
As a country with a majority Muslim population, Ramadan and Eid al-Fitr brings its own blessings. Economic activity has increased due to the high consumption of society, especially in related sectors, such as the food and beverage sector. Various studies, both national and international, were conducted to determine how the holiday affects in the capital market. The holiday effect is understood as a difference in yields or stock returns that occur abnormally due to a long holiday compared to other regular holidays. Long holidays in Indonesia occur during Eid al-Fitr. This study aims to determine whether the holiday effect occurs in the Indonesian capital market. Observation of data on the food & beverage sector in the Indonesian capital market was carried out by conducting the One Way ANNOVA test. The results of the calculation show F = 0.203 and the significance of 0.653 is greater than a = 0.05, so that rejecting H1 is due to no significant influence or no holiday effect on the Indonesian capital market